Hiking waterfalls Utah 2024 : a guide to the state's best waterfall hikes - Green, Stewart M. (Falcon Guides, 2024)
"Hiking Waterfalls Utah includes detailed maps and hike descriptions for 50 easy-to-follow waterfall hikes in the state"--